Improving androgenesis‐mediated doubled haploid production efficiency of FCV tobacco (Nicotiana tabacum L.) through in vitro colchicine application. Issue 6 (18th October 2013) - Sood, Salej; Dwivedi, Samresh; Reddy, Thamalampudi Venkata; Prasanna, Panuganti Satya; Sharma, Navin; Friedt, W.
Abstract Production of doubled haploid plants through androgenesis in flue‐cured Virginia (FCV) tobacco is a promising and convenient alternative to conventional selfing techniques for the generation of absolute homozygous lines. Here, we show a robust in vitro haploid and doubled haploid development protocol in FCV tobacco with major emphasis on improving the efficiency of chromosome doubling using in vitro colchicine treatment. We used five FCV tobacco hybrids for comparison of colchicine treatments. The anther culture response varied with developmental stages of the buds, and the highest response was observed in stage 2 buds. The effect of cold pretreatment was significant, and 4 days of pretreatment was optimum for gametic embryogenesis. Among the methods used for determining the ploidy status of plants, flow cytometry was found to be easy, fast and reliable for high‐throughput screening of haploids. Doubled haploids regeneration percentage varied from 6.77 to 11.95 in in vivo treatment, while the range of variation was 22.11% to 28.40% in in vitro colchicine treatment. We observed a pronounced increase in plant survival and the proportion of doubled haploid plants in in vitro treatment compared with the standard in vivo approach.